Fault Tolerant Line-Based Barrier Coverage Formation in Mobile Wireless Sensor Networks. (4th October 2015) - Shen, Jie; Wang, Zhibo; Wang, Zhi
Abstract : Barrier coverage is a fundamental problem for lots of applications in wireless sensor networks. In reality, sensor nodes' true locations may not be known to us considering that not every sensor node is equipped with a GPS. The measured locations of sensor nodes obtained by applying node localization algorithm often have errors, which makes it difficult to form a line-based barrier with mobile sensor nodes. In this paper, we study how to efficiently schedule mobile sensor nodes to form a barrier when sensor nodes suffer from location errors. We explore the relationship between the existence of uncovered hole and location errors and find that the lengths of uncovered holes are decided by the cumulative location errors. We also propose a method in frequency domain to efficiently calculate the distributions of the cumulative location errors. The possibility of the existence of uncovered holes can be derived by analyzing the step responses of the cumulative location errors. Extensive experimental results demonstrate the effectiveness of the proposed algorithm.